2014
DOI: 10.4049/jimmunol.1400044
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Dependent Enhanced Migratory Capacity of Th17 Cells from Children with Lupus Nephritis

Abstract: Th17 cells infiltrate the kidneys of patients with lupus nephritis (LN) and are critical for the pathogenesis of this disease. In this study, we show that enhanced activity of Stat3 in CD4+CD45RA−Foxp3− and Foxp3low effector T cells from children with LN correlates with increased frequencies of IL-17–producing cells within these T cell populations. The levels of retinoic acid-related orphan receptor c and IL-17 mRNA are significantly higher in PBMCs from children with LN than in those from controls. Mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Similarly, studies examining a T cell‐specific mTORC1 deletion found impaired Th17 and Th1 differentiation but increased iTreg differentiation 30 , 31 . Finally, IL‐17‐producing T cells from children with Lupus nephritis show enhanced activation of the AKT/mTOR signaling pathway and an enhanced migratory capacity that could be reduced by inhibition of AKT activity 32 …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, studies examining a T cell‐specific mTORC1 deletion found impaired Th17 and Th1 differentiation but increased iTreg differentiation 30 , 31 . Finally, IL‐17‐producing T cells from children with Lupus nephritis show enhanced activation of the AKT/mTOR signaling pathway and an enhanced migratory capacity that could be reduced by inhibition of AKT activity 32 …”
Section: Discussionmentioning
confidence: 92%
“…In addition, CAMKIV has been linked to expression of CCR6, which facilitates recruitment of T H17 cells to the kidney[34]. AKT inhibition reduces in vitro T H17 migration in response to CCL-20 [35], probably as a consequence of altered signaling through ROCK, which is more active in SLE T cells and is involved in CCR6 and CD44 signaling [36]. IL-17 also contributes to the loss of B cell tolerance in an autoimmune mouse [37], adding a new role to DN and T H17 cell function in SLE pathogenesis.…”
Section: Increased Numbers Of T Helper 17 Cells Promote Kidney Diseasmentioning
confidence: 99%
“…Patients with lupus nephritis have higher STAT3 activity in effector T cells and higher percentage of IL‐17‐producing cells when compared with those of controls . Moreover, the inhibition of mTORC1 signaling by rapamycin reduces both STAT3 activation in effector T cells and percentage of IL‐17‐producing T cells in lupus patients . In T‐ Rheb −/− mice, in which T cells specifically do not express Rheb, a crucial regulator of mTORC1 signaling , T cells fail to differentiate into Th17 cells, and phosphorylation of STAT3 does not occur in response to IL‐6, IL‐10, or IL‐21 .…”
Section: Stat3 and Stat5 In Mtorc1 Signalingmentioning
confidence: 99%